PENDIDIKAN KARAKTER DALAM KAJIAN BEHAVIORISTIK PERSPEKTIF PENDIDIKAN AGAMA HINDU - Ketut Agus Nova (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The education of Hindu religious character is also a rule or norms that lead people to always do good, in order to achieve a peaceful harmonious life and form a noble human being and always astiti bhakti to Ida Sang Hyang Widhi Wasa. The education of hindu religious character, is the application of sacred teachings revealed by Ida Sang Hyang Widhi Wasa that remains eternal and contains instructions about good deeds that should be carried out by Hindus and avoids reprehensible deeds and abstains from reprehensible deeds and abstains from acts that violate religious normanorma, so as to achieve perfection of physical and spiritual life. Education must shape and develop character in a better direction. In short, a complete education must be humane, not only concerning intellectual education but also subtlety of mind and inner discipline. Based on behvioristic theory considers that knowledge is objective, sure, fixed, unchanging. Knowledge has been neatly structured, so learning is the acquisition of knowledge, while teaching is transfer of knowledge to the person who is studying or students. The application of this behavioristic theory of teachers plays a more active role in the classroom, because all actions and commands ordered by the teacher will be emulated by the students. Procedures for controlling or improving behavior in hindu concepts and character content that can be done in the content: strengthening competitive behavior, exclusion, satiasi, punishment.